Effect of the Route of Inoculation on Antibody Formation in Guinea Pigs Immunized with Parainfluenza Virus Vaccines - DeMeio, Joseph L. (1968)
The efficiency of the intramuscular route of immunization of guinea pigs was compared with the intraperitoneal route when trivalent parainfluenza virus vaccine was employed as immunogen. When the routes of immunization were compared by effective dose 50, the intramuscular route was more effective. Likewise, a statistical evaluation of conversion rates and of titers revealed significantly higher values for the intramuscular than for the intraperitoneal route to all three components in two of the lots of vaccine tested.